A Note on Natural Transformation of Exton’s Triple Series Hypergeometric Function - Harsh, Harsh verdhan; Sharma, Puneet Krishna; Khan, Shabana (Nepal Journal of Mathematical Sciences, 2020)
Triple series hypergeometric functions are very important from the applications point of view. Exton had defined 20 triple hypergeometric functions namely X1 , X2 , … , X20. Integral transform technique is widely using for research purpose. Natural transform is a new kind of integral transform and generalization of Laplace transform. In the present research note, we give the Natural integrals of the triple series hypergeometric function due to Exton.